MANAJEMEN KEPEMIMPINAN DALAM MENINGKATKAN EFEKTIFITAS PEMBELAJARAN PADA MI TAHFIDZ ANWAHA - M. Arsyad; Muhammad Iqbal, Muhammad Kadrida, Muhammad Salman, Syahrani (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
Eflective leadership in education requires a commitment to continuous learning and professional development. This can help ensure that school leaders and teachers are equipped with the knowledge and skills they need to support student learning and achievement. It is the responsibility of the school principal as a leader to always strive to take good actions to improve the quality and eflectiveness of the school as a whole. The calm and pleasant atmosphere of the school environment is suitable for implementing enjoyable and useful outdoor activities. Most teachers participate in learning activities outside the classroom.